The Effectiveness of The Work of Traffic Officials in The Transportation Agency in Handling Bandung City Congestion - Feri Herdiyanto (Politeknik Siber Cerdika Internasional, 2020)
In this research, there is a phenomenon about the ineffectiveness of handling traffic problems which are the authority of the Bandung City Transportation Service. The ineffectiveness can be seen from the road arrangements, both the direction of traffic flow and the handling of problems with lights and traffic signs as well as the number of bad road vehicles that still pass on the highway. In connection with this phenomenon, the purpose of this study is to determine: 1. The effectiveness of the work of employees at the Bandung City Relations Office and 2. The factors that influence the work effectiveness of employees at the Bandung City Transportation Service. This research took place at the Department of Transportation of Bandung City. The research method used was descriptive qualitative. Data obtained from interviews the data sources were obtained from documents and informants. Research informants are the head of the Bandung traffic service and the community. Data analysis was carried out using interactive analysis techniques, which included data collection, data presentation, data reduction, and drawing conclusions. The results of the study concluded that: 1. The work effectiveness of the Bandung transportation service employees was quite good, seen from the work and implementation, the implementation of sudden tasks, the creativity of employees, job satisfaction of employees and users of community satisfaction.2. The factors that affect work effectiveness are employee job satisfaction, sudden assignments, communication and coordination between technical implementing units, cooperation in team work and between implementing units or between sections, employee creativity in completing work, facilities and infrastructure that accommodate and in accordance with needs, as well as community support in the form of road use in accordance with the rules and regulations.